La Divina Commedia: Un Autentico Itinerario Spirituale - Frisina, Marco (Lateranum, 2023)
The extraordinary side of Dante's "Divine Comedy" is mainly given by the universal character that all treated topics have and by the authentic depth that signs the way the author is describing his journey as an internal and existential itinerary. On beyond of all its literary quality, the poetic writing has to be seen as a book of high spirituality and as an emblematic summary of the entire human family concretely expressed in its various personalities. The personal crisis that Dante had to get through after Beatrice's death becomes an opportunity to face the fundamental questions of any human existence and to interprete Christian faith in the light of these interiore experiences; like that they can be shared and offered to the entire world through poetic language. Since ever the Pontifical Teaching has indicated Dante's poem as a highly spiritual text to consider with emphasis and to penetrate in all its aspects. Therefore it's necessary to reread the Comedy not only as a master piece of literature but also as a book of spirituality where philosophy and theology turn to be valid instruments and interior guide lines. (English)